Gendered homophobia in sport and coaching: Understanding the everyday experiences of lesbian coaches - Norman, L. (International Review for the Sociology of Sport, 2012)
The purpose of this article is to discuss a theory of everyday gendered homophobia as a way of understanding lesbian coaches` experiences of their profession. I discuss the need to gain a better comprehension of homophobia achieved through deconstructing women`s day-to-day experiences of professional coaching, examining how their lives are individually organized along multiple power lines, namely sexual orientation and gender. Through this, it is possible to connect the macro-structure of sport to the micro- and recognize the everyday inferiorizations that take place within the participants` lives. The main focus of the article is to explore the power of understanding the everyday and present the key conceptual issues and processes underpinning a theory of everyday gendered homophobia. The conception of everyday gendered homophobia is based upon data from in-depth semi-structured interviews with 10 professional women coaches who identified themselves as lesbian, from both individual and team sports within the UK.